Business information systems : analysis, design, and practice - Curtis, Graham; Cobham, David P. (Harlow, Essex, England : Pearson Education, 2008)
This book aims to equip those in, or entering business to assess the opportunities, limitations and major issues surrounding modern business information systems and to appreciate the way that information systems can aid the realization of business objectives.
Information systems -- Strategy and information systems -- Business information technology -- Distributed systems, networks and the organization -- The Internet and the World Wide Web -- Electronic commerce and business -- Business intelligence -- File organization and databases for business information systems -- File organization and databases for business information systems -- Information systems: control and responsibility -- Information systems development: an overview -- The systems project: early stages -- Process analysis and modelling -- Data analysis and modelling -- Data analysis and modelling -- Systems design -- Detailed design, implementation and review -- Object oriented approaches -- Systems development: further tools, techniques and alternative approaches -- Expert systems and knowledge bases.
Includes bibliographical references and index.
1
Keywords: Business -- Data processing; Information storage and retrieval systems -- Business; Management information systems; System design; System analysis; Expert systems (Computer science)